The Ideal Concept of the Position Judges as State Officials in the Ius Constituendum in Indonesia - H. Adies Kadir (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
Problems regarding the position of judges that continue to continue will affect their duties in upholding law and justice. Provisions regarding the position of judges in several statutory provisions are also considered to have multiple interpretations and are inconsistent. To find out more fully, this paper will first analyze and criticize the concept of judges in the Draft Law on the Office of Judges, then provide the ideal concept of the position of judges as state officials in the ius constituendum in Indonesia. This study uses normative legal research with a statutory and conceptual approach. The results of the study are tThere are several crucial issues in the Draft Law on the Position of Judges, which among others are related to 1) The Government's Rejection of the Status of all Judges as State Officials; 2) Periodization of the position of Supreme Court Justices; 3) Sharing of Judges Recruitment Authority with the Judicial Commission; and 4) Reduction of Judge's Retirement Age. Then to realize the ideal position of judges in the future in the ius constituendum, changes need to be made through changes in concepts ranging from; 1) the concept of judges as State Officials; 2) Supreme Court Institutional Structure; 3) Mechanism of Promotion, Demotion, Mutation, Reword and Punishment of Judges; 4) Strengthening the Retirement Age of Judges in Indonesia; 5) Court of Appeals and Classification of Cases Entering the Supreme Court; 6) The concept of the Judicial Commission in Maintaining Judges' Dignity; 7) Regulation of Ad Hoc Judges and Special Courts in Indonesia; and 8) Recruitmentand Education of Candidates for Judges.